Boablingin Sings of The Helong Soul : A Semiotic And Cultural Reading of A Traditional Song: English - Lasi, Apri Marleni; Isu, Rudolof Jibrael; Radja, Markus Dimu (Universitas Persatuan Guru 1945 NTT, 2025)
This research explores the cultural, semiotic, and social meanings embedded in the traditional song